Knowledge, attitude and willingness to donate organ among medical students of Jimma University, Jimma Ethiopia: cross-sectional study - Fantu Kerga Dibaba; Kabaye Kumela Goro; Amare Desalegn Wolide; Fanta Gashe Fufa; Aster Wakjira Garedow; Birtukan Edilu Tufa; Eshetu Mulisa Bobasa (BMC, 2020)
Abstract Background The lack of organ donors has become a limiting factor for the development of organ transplantation programs. Many countries are currently facing a severe shortage of organs for transplantation. Medical students, as future doctors can engage in the role of promoting organ donation by creating awareness and motivating the community to donate their organs besides their voluntary organ donation. The aim of this study is to assess the knowledge, attitude and willingness of undergraduate medical students' towards organ donation at Jimma University. Methods A cross-sectional study was conducted among 320 medical students from year I to internship using questionnaire in order to assess their knowledge, attitude and willingness regarding organ donation. Data collected was entered using epidata and analyzed using Statistical Package for Social Sciences (SPSS) software version 20. Results Mean (±SD = standard deviation) age of participants was 23.48 ± 17.025 years. 57.8% of the study subjects were male. There was a statistically significant interaction effect between gender and year of study on the combined knowledge questions (dependent variables) F(25,062) = 1.755,P = 0.014, Wilk's Λ = .033. Variables which were related to a positive attitude towards organ donation were: being of the male sex (Odds Ratio = 1.156); having awareness about organ donation (Odds Ratio = 2.602); not having a belief on the importance of burying intact body (Odds Ratio = 5.434); willingness to donate blood (Odds Ratio = 4.813); and willingness to donate organ (Odds Ratio = 19.424). Conclusion High level of knowledge but low level of positive attitude and willingness was noticed among the study participants toward organ donation.